Hypermature Intumescent Cataract in Advanced Keratoglobus - Singh, Bhupesh (Int Med Case Rep J, 2020)
We report a rare case of bilateral keratoglobus with hypermature intumescent cataract in a 55-year-old woman. Clinical examination and corneal topography confirmed generalized corneal bulging and global corneal thinning. A Pentacam® (Oculus Optikgerate, Wetzlar, Germany) demonstrated bilateral diffuse corneal thinning (368 μm in the right eye and 371 μm in the left eye). Phacoemulsification was performed in the right eye after thorough workup and modification of the surgical technique. This case report helps in better understanding of the challenges of cataract surgery and intraocular lens selection in a keratoglobus patient, and stresses the need for both thorough preoperative planning and intraoperative surgical modifications.